Socio-Environmental Risks Linked with Mine Tailings Chemical Composition: Promoting Responsible and Safe Mine Tailings Management Considering Copper and Gold Mining Experiences from Chile and Peru - Cacciuttolo, Carlos (2023)
There is a need to define mine tailings in a clear, precise, multidisciplinary, transdisciplinary, and holistic manner, considering not only geotechnical and hydraulic concepts but also integrating environmental and geochemical aspects with implications for the sustainability of mining. This article corresponds to an independent study that answers questions concerning the definition of mine tailings and the socio-environmental risks linked with mine tailings chemical composition by examining the practical experience of industrial-scale copper and gold mining projects in Chile and Peru. Definitions of concepts and analysis of key aspects in the responsible management of mine tailings, such as characterization of metallic–metalloid components, non-metallic components, metallurgical reagents, and risk identification, among others, are presented. Implications of potential environmental impacts from the generation of acid rock drainage (ARD) in mine tailings are discussed. Finally, the article concludes that mine tailings are potentially toxic to both communities and the environment, and cannot be considered as inert and innocuous materials; thus, mine tailings require safe, controlled, and responsible management with the application of the most high management standards, use of the best available technologies (BATs), use of best applicable practices (BAPs), and implementation of the best environmental practices (BEPs) to avoid risk and potential socio-environmental impact due to accidents or failure of tailings storage facilities (TSFs).